Cryoresistance and potential vitrification in lichen thalli - Sekerák Jr., Jiří; Hájek, Josef; Barták, Miloš; Zámečník, Jiří; Faltus, Miloš; Puhovkin, Anton; Parnikoza, Ivan (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):234